Pengujian Fungsional Aplikasi Inventory Barang Kedatangan Dengan Metode Black Box Testing Bagi Pemula - Nur Muhammad Arofiq; Reyven Ferdo Erlangga; Ade Irawan; Masuhan; Aries Saifudin (CV. Multi Kreasi Media, 2023)
There are several testing techniques for Black Box Testing, including Equivalent Partitions Testing, Boundary Value Analysis Testing, Comparation Testing, Sample Testing, Robustness Testing and others. Here it is selected using the Equivalence Partitions Technique which is only to test whether there are errors in: system functions, Interface, data structure or data access, performance, initialization. The object being tested is the Library Information System via the web. The number of forms tested was 3 pieces, namely the login form, the added item form and the item edit form where each form was tested by entering some input data that often occurs (found). The results showed that testing the software using the Black Box Testing method with the Equivalence Partitions Technique in the arrival goods input application still has a form whose output results are not as expected in the design due to an error. From the results of calculating the validity of the system, a value of 75% is obtained. The possibility of an error that occurs is due to an error in the line of code (syntax). For this reason, it is necessary to update the syntax to fix the bug.